2018
DOI: 10.1371/journal.pone.0210002
|View full text |Cite
|
Sign up to set email alerts
|

Yeast screening and cell immobilization on inert supports for ethanol production from cheese whey permeate with high lactose loads

Abstract: Eight yeast strains of the genera Saccharomyces and Kluyveromyces were screened to ferment high lactose-load cheese whey permeate (CWP) (>130 g/L lactose) without nutrient supplementation. The fermentation conditions (temperature, pH and time) were optimized to maximize the fermentation performance (ethanol titer, ethanol yield and lactose consumption) for the two preselected strains, K. marxianus DSM 5422 and S. cerevisiae Ethanol Red, using a response surface methodology (RSM). Under optimized conditions, K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…In the NF retentate, under mild oxygen-limiting conditions, the strain was unable to exhaust lactose (30% of lactose remains in the medium at 120 h fermentation). It is important to note that the ethanol yield and productivity values determined in our study for the reference strain K. marxianus CBS 397 are similar to those reported by other researchers for fermentations with this strain in synthetic medium with 200 g/L lactose and 0.2 vvm aeration (0.43 g/g and 2.12 g/L/h, respectively) [38], and in concentrated whey powder (0.44 g/g and 1.3 g/L/h, respectively) [27]. Comparable parameters were also reported for fermentation of cheese whey, despite the lower lactose content (50 to 59 g/L) [28,39].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the NF retentate, under mild oxygen-limiting conditions, the strain was unable to exhaust lactose (30% of lactose remains in the medium at 120 h fermentation). It is important to note that the ethanol yield and productivity values determined in our study for the reference strain K. marxianus CBS 397 are similar to those reported by other researchers for fermentations with this strain in synthetic medium with 200 g/L lactose and 0.2 vvm aeration (0.43 g/g and 2.12 g/L/h, respectively) [38], and in concentrated whey powder (0.44 g/g and 1.3 g/L/h, respectively) [27]. Comparable parameters were also reported for fermentation of cheese whey, despite the lower lactose content (50 to 59 g/L) [28,39].…”
Section: Resultssupporting
confidence: 90%
“…To study the ability of Kluyveromyces strains to directly use NF and RO retentates as a substrate for ethanol production (without supplementation), the following ten lactose-fermenting strains were selected from a yeast culture collection (PYCC): five K. marxianus strains and five K. lactis strains (Table 1). The K. marxianus CBS 397 (PYCC 3884) strain was expressly included in this screening for benchmarking, as this strain has been often described as one of the best lactose-fermenting yeasts, both in terms of ethanol production rate and maximum ethanol titer [27,28,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…If we assume that between 5% and 10% of milk consumption in the country is used for cheese production, between 429,000 kg and 857,000 kg of cheese is produced in Jamaica annually. About 10 liters of cheese whey are generated for each kg of cheese manufactured; thus, the amount of cheese whey in the country could be in the range of 4.3 and 8.6 million liters per year (Díez-Antolínez et al 2018). Lactose content in cheese whey is about 0.05 kg/liter, on average, thus between 215,000 kg and 430,000 kg of lactose could be generated annually (Koushki 2012).…”
Section: Food and Beverage Wastesmentioning
confidence: 99%
“…Similarly, Diez-Antolinez et.al (2018) screened different yeast and immobilization materials for ethanol production from cheese whey permeate. They reported that Glass Rasching rings and alumina beads showed stable performance over 1,000 hours, yielding ethanol titers of 60 g/L, which substantially reduced yeast cultivation costs (Diez-Antolinez, et al, 2018). The economic benefits associated with cell immobilization and recycling, such as increased yields and productivities and lower capital costs due to shorter residence times should encourage researchers to do further, detailed techno-economic analyses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%